User Experience Studies of Advanced Interactive Multimedia Features on Mobile Travel Guide Application - Angeline, Lee Ling Sing (Universiti Malaysia Sarawak, (UNIMAS), 2017)
The use of modern interactive mobile travel application is becoming a necessity of many destinations to stay competitive and attractive to the modern tourists. Nonetheless, many travel applications suffer from usability issues, such as complex interfaces, information overload and limited interaction mechanisms. Henceforth, the objectives of this research were to identify user’s requirements on interactive mobile travel application; to investigate the usability issues of travel application in the market; to design and develop a tangible mobile application prototype of Sarawak Travel; and finally to evaluate tourists’ experiences on the prototype development. Analyzing reliability, validity factor, and One-Way Within Subjects ANOVA were conducted to determine the types of interactive multimedia features and the significant differences amongst the travel applications sampling. Findings showed a significant effect among the three sample travel applications, with reading of Wilks’ Lambda = 0.35, F (2, 28) = 25.23, p = 0.00 and paired samples Ttests were conducted to compare the three post hoc test. Results indicated that interface design type does have an effect on user experience. Results indicated that the type of interface design does have an effect on user experience, where applications with the most familiar function and the simplest, straight forward visual display were thought to be the most effective, efficient, and satisfaction from participants. Hence, a prototype of mobile travel guide application was developed based on the previous studies. The evaluation showed a potential high demand of integrating advanced interactive multimedia features on mobile tourism application to attract, engage, and encourage regular usage in the tourism industry.